The role of dual-mobility in primary total hip arthroplasty - Momoli, Alberto; Mulone, Alessio; Ulgelmo, Maurizio; Lunardelli, Enrico; Ambrosini, Carlo; Giaretta, Stefano (Lo Scalpello - Journal, 2021)
Total hip arthroplasty (THA) is one of the most successful surgical procedures in orthopedic surgery. However, to date, instability remains one of the main causes of failure of the first im- plant, leading to a high number of surgical revisions and causing serious discomfort for the patient.The dual mobility (DM) implant, designed in France by Prof G. Bousquet and Lng A. Ram- bert in the 1970s, has shown excellent results in reducing the rate of prosthetic dislocations. The first generation of dual mobility, however, was burdened by a series of complications that limited its use in some categories of high-risk patients.Over the years, the evolution of prosthetic design and the gradual improvement of materials have made it possible to extend the indications of this type of implant to other categories of patients.In view of the advantages encountered with the use of dual mobility, this could represent a valid strategy to be adopted in hip prosthetic surgery.